Transradial Retrograde Percutaneous Coronary Intervention of Chronic Total Occlusion via an Ipsilateral Septal Collateral Using a Single Guiding Catheter: A Case Report - Liu, Xiaogang; Zhang, Jing; Zhang, Hong; Zhang, Peng; Fu, Naikuan (Frontiers in Cardiovascular Medicine, 2022)
Background: With the development of specialized equipment and the retrograde technique, success rates for percutaneous coronary intervention (PCI) of chronic total occlusions (CTO) have increased from 60% to 90% in the past 10 years. Performing PCI via a collateral channel from the contralateral artery, using two guiding catheters, is usually the preferred approach to retrograde CTO-PCI. In the case described in this report, only the ipsilateral septal collateral artery from the proximal occluded left anterior descending (LAD) artery was available. The procedure can be performed successfully from radial artery access using a single guiding catheter. Case Summary: A 57-year-old patient, with a history of anterior and inferior myocardial infarction and previous PCI, underwent a planned coronary arteriography due to his complaints of typical angina symptoms. Coronary angiography revealed stent occlusion located mid-LAD and severe in-stent restenosis in the distal right coronary artery (RCA). A proximal septal branch was supplying the distal LAD retrogradely. After repeated failed attempts at antegrade PCI for the LAD’s CTO, the retrograde approach was tried. This intervention finally succeeded through the ipsilateral septal collateral. It was preformed via a single radial-artery access throughout the whole process. Postoperatively, the patient had no complications, and was stable at one-year follow-up. Conclusion: The transradial approach to retrograde PCI for CTO, via an ipsilateral septal collateral using a single guiding catheter, is feasible and safe in appropriately selected cases.